2011
DOI: 10.1186/1471-2164-12-524
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic effects of di-(2-ethylhexyl)-phthalate in Syrian hamster embryo cells: an important role of early cytoskeleton disturbances in carcinogenesis?

Abstract: BackgroundDi-(2-ethylhexyl)-phthalate (DEHP) is a commonly used plasticizer in polyvinylchloride (PVC) formulations and a potentially non-genotoxic carcinogen. The aim of this study was to identify genes whose level of expression is altered by DEHP by using a global wide-genome approach in Syrian hamster embryo (SHE) cells, a model similar to human cells regarding their responses to this type of carcinogen. With mRNA Differential Display (DD), we analysed the transcriptional regulation of SHE cells exposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 76 publications
1
15
0
Order By: Relevance
“…It was previously reported that MEHP is able to destroy the ES between rat Sertoli cells and spermatogenic cells, causing a release of the immature germ cells into the seminiferous tubule, which weakens reproductive function (35,36). The present study indicated that the expression of the genes that encode actinin and vinculin was decreased by MEHP, which was similar to the results of a previous study, in which Syrian hamster embryo cells were exposed to 50 µM DEHP for 24 h, revealing that the downregulated genes were associated with focal adhesion or cell junctions (37). This indicates that MEHP may affect the ECM-receptor interaction and focal adhesions to disrupt intercellular junctions and the formation of fissures between Sertoli cells and spermatogenic cells, resulting in the loss of spermatogenic cells from the seminiferous epithelium.…”
Section: Discussionsupporting
confidence: 88%
“…It was previously reported that MEHP is able to destroy the ES between rat Sertoli cells and spermatogenic cells, causing a release of the immature germ cells into the seminiferous tubule, which weakens reproductive function (35,36). The present study indicated that the expression of the genes that encode actinin and vinculin was decreased by MEHP, which was similar to the results of a previous study, in which Syrian hamster embryo cells were exposed to 50 µM DEHP for 24 h, revealing that the downregulated genes were associated with focal adhesion or cell junctions (37). This indicates that MEHP may affect the ECM-receptor interaction and focal adhesions to disrupt intercellular junctions and the formation of fissures between Sertoli cells and spermatogenic cells, resulting in the loss of spermatogenic cells from the seminiferous epithelium.…”
Section: Discussionsupporting
confidence: 88%
“…SHE cell assay data further support links between one-carbon metabolism and cell transformation. SAH hydrolase is a tumor suppressor enzyme [81] reported to downregulate in di(2-ethylhexyl)phthalate (DEHP)-treated SHE cells [82]. Choline is known to be an important cellular metabolite and methyl donor in the one-carbon metabolism pathway, and diethanolamine reduces the uptake of choline to induce SHE cell morphological transformation [83].…”
Section: Methyltransferasesmentioning
confidence: 99%
“…Due to the complexity of events that together contribute to chemical carcinogenesis, it is unlikely that a single method will be able to provide enough information about diverse events/mechanisms of actions and possible interactions [ 9 , 10 , 11 ]. Particularly, several studies have combined cellular transformation experiments using different cell lines with the transcriptome profiling, in order to explore the malignant transformation process [ 10 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%